1994
DOI: 10.1002/1097-0142(19941015)74:8<2276::aid-cncr2820740811>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase plasminogen activator as a prognostic marker in different subgroups of patients with breast cancer

Abstract: Background. Urokinase plasminogen activator (uPA) is a serine protease involved in cancer invasion and metastasis. Previously, uPA was shown to be an independent prognostic marker in breast cancer. The aim of this study were to evaluate uPA as a prognostic marker in different subgroups of patients with breast cancer. Methods. Urokinase plasminogen activator was as sayed by enzyme‐linked immunosorbent assay in detergent extracts of human breast tumors. Results. Using both disease free interval (DFI) and overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
125
2
2

Year Published

1996
1996
2001
2001

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(137 citation statements)
references
References 20 publications
8
125
2
2
Order By: Relevance
“…Urokinase and its inhibitors have been proposed as new prognostic factors in breast cancer (Duffy et al, 1990;Janicke et al, 1990;Foekens et al, 1992;Spyratos et al, 1992;Bouchet et al 1994;Foekens et al, 1995). However, their use for this purpose can only be envisaged once the results obtained with different assay methods have been compared.…”
Section: Discussionmentioning
confidence: 99%
“…Urokinase and its inhibitors have been proposed as new prognostic factors in breast cancer (Duffy et al, 1990;Janicke et al, 1990;Foekens et al, 1992;Spyratos et al, 1992;Bouchet et al 1994;Foekens et al, 1995). However, their use for this purpose can only be envisaged once the results obtained with different assay methods have been compared.…”
Section: Discussionmentioning
confidence: 99%
“…In a preliminary report, in 1988, evidence was presented that high uPA enzyme activity in breast carcinoma extracts correlated with a shortened diseasefree interval for the patients [14]. Tw o years later, in 1990, two groups of investigators j Jänicke and co workers and Duffy and coworkers independently reported measurements of uPA antigen content in breast cancer tissues [15,24]. Applying completely different uPA ELISAs, these authors reported that a high level of immunoreactive uPA is significantly correlated with high relapse rate and associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical and pathophysiological relevance of such qualities that carry the potential for metastasis is as yet unknown. In the fascinating process of metastasis, many researchers have focused on proteases and adhesion molecules (uPA, cathepsin D, integrins, E-cadherin) (Needham et al, 1988;Duffy et al, 1990). The uPA system is one of the most extensively investigated families of proteases that are secreted in tumour tissue.…”
mentioning
confidence: 99%